Adolescents and self-hurt behaviour: a study among adolescents in Penang - Guan, Teik Ee; See, Ching Mey; Lau, Poh Li (Penerbit Universiti Utara Malaysia, 2016)
The adolescence stage is described as the “storm and stress” stage because despite rapid growth in the physical body, adolescents are emotionally vulnerable. In the ever changing and diverse society, adolescents need to handle challenges and problems of family, school, and friends. Emotional or mental pain could cause many side effects. One of the side effects is adolescents trying to hurt themselves when they cannot handle problems. Concern about young people engaging in self-hurt behaviour has prompted many researchers to carry out studies in the west. In Malaysia, the subject of self-hurt is taboo, and self-hurt is still not an easy topic to discuss publicly. Even though Malaysia has a relatively young population as compared to the west, little of the aetiology of self-hurt among young population has been researched. To date, the state of well-being of our adolescents is uncertain. This study is therefore carried out using an instrument named Self-Hurt Assessment to investigate whether self-hurt problems exist among 602 school-going adolescents aged 13-16 in 12 schools in the state of Penang, Malaysia. The results and the implications are discussed.